Obstacles to state-building in the African Sahel: An analytical study before, during, and after colonization - Benani, Houria (The International tax journal, 2025)
The process of state-building in the Global South has passed through several phases. In some cases, this process gained momentum, while in others, it faced stagnation and hesitation. In many instances, states were exposed to risks and threats that weakened their structure and questioned their survival. These threats also reduced their performance and undermined their regional and international standing. The Sahel region of Africa has not been immune to these challenges. It has become a hotspot for crime, the spread of terrorism, drug and human trafficking, and rising migration rates. These problems can be traced back, in part, to the colonial era, which bears responsibility for many of the current issues. Additionally, the post-independence period brought with it several obstacles that affected the state's stability and development across economic, social, and military dimensions.